Analysis of critical-creative thinking styles and their implications on self efficacy teacher pree service. Issue 1 (January 2021) - Hamid, A.; Saputro, S.; Ashadi; Masykuri, M.
Abstract: Critical-creative thinking styles and self-efficacy are important things in facing the 4.0 industrial revolution. This study conducted to analyze the critical-creative thinking style and its implications for prospective teachers' self-efficacy. The method used is a survey method. The instrument for creative-critical thinking using Yanpiaw Creative-critical Styles (YCCS) test. The YCCS instrument has standardized with critical-creative thinking skills tests such as WGCTA (The Watson-Glaser Critical Thinking Appraisal) and TTCT (Torrance Test Creative Thinking). The results of the analysis show that (1) student-teacher prospective teachers do not have a supercritical or super creative thinking style, (2) prospective pre-service teacher are more dominant in having an intermediate thinking style, (3) pre-service teacher with a higher critical-creative thinking style have more significant implication for self-efficacy, compared intermediate thinking style.